2022
DOI: 10.1186/s41256-022-00240-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and validation of the Community Maternal Danger Score algorithm

Abstract: Background High rates of maternal mortality in low-and-middle-income countries (LMICs) are associated with the lack of skilled birth attendants (SBAs) at delivery. Risk analysis tools may be useful to identify pregnant women who are at risk of mortality in LMICs. We sought to develop and validate a low-cost maternal risk tool, the Community Maternal Danger Score (CMDS), which is designed to identify pregnant women who need an SBA at delivery. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This can be attributed to the various successful maternal health interventions by government and non-government agencies that have been implemented in these facilities in a bid to reduce the high MMR of Benue state [ 17 , 18 ]. Recent reports have shown that the maternal mortality ratio (MMR) in Benue State is as high as 1189 per 100,000 population, making the state one of the highest contributors to the national average of 576 deaths per 100,000 [ 17 , 19 ]. As a result of this, several strategies have been implemented by government and non-government agencies (including Meta) to contain the menace [ 17 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the various successful maternal health interventions by government and non-government agencies that have been implemented in these facilities in a bid to reduce the high MMR of Benue state [ 17 , 18 ]. Recent reports have shown that the maternal mortality ratio (MMR) in Benue State is as high as 1189 per 100,000 population, making the state one of the highest contributors to the national average of 576 deaths per 100,000 [ 17 , 19 ]. As a result of this, several strategies have been implemented by government and non-government agencies (including Meta) to contain the menace [ 17 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Records from the World Health Organization indicate that sub-Saharan Africa accounts for 66% of global maternal deaths, with a maternal mortality ratio of 546 per 100,000 live births [ 1 ]. The Nigerian maternal mortality ratio is 512 per 100,000 live births [ 2 ], while we report a maternal mortality ratio for Benue State, one of Nigeria’s 36 states, of 1,189 per 100,000 live births [ 3 ]. The National Demographic and Health Survey reveals that Nigeria constitutes approximately 1% of the world population yet accounts for 10% of the world maternal mortality [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of routinely collected maternal data can identify pregnant women who are at risk of mortality or morbidity [ 3 ]. The Community Maternal Danger Score (CMDS) is a low-cost, evidence-based maternal risk analysis tool that was validated in Makurdi, Nigeria to predict the need for skilled birth attendance and identify high risk for maternal death [ 3 ]. The CMDS has been developed into a scoring tool that is available as an Android application to encourage pregnant women to deliver with SBAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation